2008
DOI: 10.1109/tro.2008.2003269
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Limitations on Designing Optimally Fault-Tolerant Redundant Manipulators

Abstract: Abstract-In this paper, the authors examine the problem of designing nominal manipulator Jacobians that are optimally fault tolerant to one or more joint failures. Optimality is defined here in terms of the worst-case relative manipulability index. While this approach is applicable to both serial and parallel mechanisms, it is especially applicable to parallel mechanisms with a limited workspace. It is shown that a previously derived inequality for the worst-case relative manipulability index is generally not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 43 publications
1
53
0
Order By: Relevance
“…In ref. [33], the upper limit of an optimal fault-tolerant configuration for redundant manipulators has been studied and it has indicated that the optimal fault-tolerant configuration is not possible for manipulators with more than 12-DOR. In general, the higher the degree of redundancy, the better fault tolerance of the manipulators.…”
Section: Kinematic and Self-motion Manifoldsmentioning
confidence: 99%
See 2 more Smart Citations
“…In ref. [33], the upper limit of an optimal fault-tolerant configuration for redundant manipulators has been studied and it has indicated that the optimal fault-tolerant configuration is not possible for manipulators with more than 12-DOR. In general, the higher the degree of redundancy, the better fault tolerance of the manipulators.…”
Section: Kinematic and Self-motion Manifoldsmentioning
confidence: 99%
“…For instance, some properties of the Jacobian matrix for fault tolerance have been used in refs. [14,29]. The relationship between the fault tolerance and the null space of Jacobian matrix has been addressed.…”
Section: Kinematic and Self-motion Manifoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to study equally fault-tolerant configurations, we use the following result, which was proved in [20]:…”
Section: Designing Optimally Fault-tolerant Manipulator Jacobiansmentioning
confidence: 99%
“…Unfortunately, the requirement that q is an integer automatically eliminates most spatial manipulator designs since only specific values of r are feasible. Indeed, it was shown in [20] that regardless of a manipulator's geometry or the amount of kinematic redundancy present in a manipulator, no fully spatial manipulator Jacobian can be equally faulttolerant to two joint failures. In this article, we will examine the cases when the workspace has dimension m =2and 3.…”
Section: Designing Optimally Fault-tolerant Manipulator Jacobiansmentioning
confidence: 99%